Standardised syringin-rich tinospora crispa aqueous extract with antioxidant, anticholesterol and antiatherosclerotic properties / Zamree Md Shah - Md Shah, Zamree (2019)
Tinospora crispa or known as Patawali is one of medicinal plants which are rich of bioresource for traditional systems of medicine, food supplements and pharmaceutical preparations. According to scientific researches, the stem of this plant is proven to possess many beneficial bioactivities and has great potential to be used in developing naturally occurring commercial products in market demand. However, very little research has been carried out with regards to the extraction procedure to obtain the optimum extraction yield with high content of its bioactive compound that can be further used in preparing standardized extract of this plant. Knowledge of its active compound and the mode of action that responsible to the desired effects is remains unfold. This study aimed to prepare the standardised Tinospora crispa aqueous extract (STCAE) and to investigate its anti-oxidant, anti-cholesterol and anti-atherosclerotic properties. Experiments were carried out to determine the effects of various operating parameters on the qualitative and quantitative aspects of T. crispa stems. Syringin was selected as the quality indicator in this study because this compound played a major role in bioactivities of Tinospora crispa including anti-hypertension, free radicals scavenging, anti-diabetic and anti-inflammatory. The optimum extraction conditions of T. crispa stems were determined as 60 °C, 1 hour of extraction time and the ratio of water to solid is 15:1 (ml:g). STCAE was produced on the basis of the extract containing at least 0.4 wt % of syringin. STCAE was found to possess high antioxidant activities through DPPH, FRAP and TBA bioassays. Cytotoxic study performed revealed that STCAE was not toxic to the cell. Through cell culture experiment, STCAE and syringin showed strong cholesterol reducing effects demonstrated by a significant increase in molecules levels involved in reverse cholesterol transport (Apo A1, LCAT, LDL-R, SRB-1 and HL). The efficacy of these activities is appreciably good when compared with standard drug simvastatin. However, STCAE and syringin showed moderate effect in controlling mevalonate pathway. The anti-cholesterol and anti-atherosclerotic properties of STCAE were further investigated in vivo using rabbits. The hypercholesterolemic rabbits were induced and the rabbit were given different concentration of STCAE (200, 450 and 600 mg/kg) for 10 weeks. Results from lipid analysis showed that the levels of total cholesterol (TC), triglyceride (TG) and LDL of the hypercholesterolemic rabbits were significantly reduced with the treatment of STCAE at all concentrations while HDL levels was elevated compared to hypercholesterolemic group. Through plasma analysis, the activity of gamma glutamyl transferase (GGT) and alkaline phosphates (ALP) were also reduced significantly with the treatment of STCAE at all concentration compared to hypercholesterolemic group. All group of rabbits tested with STCAE showed significantly high total antioxidant status (TAS), glutathione peroxidase (GPx) and superoxide dismutase (SOD) activities. Among the concentrations of STCAE tested, medium dose (450 mg/kg) showed more potent effect in reducing blood serum TC, TG and LDL levels and increasing HDL levels compared to low and high dosages counterparts. No foam cell formation was visible in aorta of rabbits treated with STCAE in dose dependent manner. The compound that donates to the desired effects possibly contributed by syringin. The results obtained suggested that STCAE could be used as an easily accessible source of natural antioxidants and possible supplement by pharmaceutical industry for the management of hypercholesterolemia.